Emotional Response and Changes in Heart Rate Variability Following Art-Making With Three Different Art Materials - Haiblum-Itskovitch, Shai; Czamanski-Cohen, Johanna; Galili, Giora (Frontiers in Psychology, 2018)
Art therapy encourages the use of art materials to express feelings and thoughts in a supportive environment. Art materials differ in fluidity and are postulated to thus differentially enhance emotional response (the more fluid the material the more emotion). Yet, to the best of our knowledge, this assumption has not been empirically tested. The current study aimed to examine the emotional and physiological responses to art making with different art materials. We were particularly interested in vagal activity, indexed by heart rate variability (HRV), because of its association with numerous health related outcomes. In this study, fifty adults (mean age 33 ± 10.27 years, 52% males) participated in a repeated measures experiment, in which they were requested to draw with three art materials (order randomized) differing in their level of fluidity (pencil, oil-pastels and gouache paint) intermittent with periods of music. We measured the emotional response to art making with each material using a self-report measure and matrices of HRV using a wearable electrocardiogram (ECG) device. We calculated two indices of HRV, one indicative of parasympathetic nervous system (PNS) activity, and one indicative of sympathetic nervous system (SNS) activity. Art making with gouache paint and oil pastels resulted in improved positive mood, while pencil did not. Art making explained approximately 35% of the variability in parasympathetic reactivity, which may indicate changes in emotional regulation processes during the art-making task. Yet, fluidity was not sufficient to explain the reaction to art-making. Surprisingly, the largest suppression of PNS and augmentation of the SNS occurred during art-making with oil-pastels and not with Gouache. Moreover, PNS and SNS reactivity to oil-pastels were related to emotional valance, which may point to emotional engagement. We can conclude that art-making with oil-pastels, first created in Japan in 1924 to increase self-expression of students, results in a unique emotional and physiological responses. These findings might be explained by the enhanced tactile experience of art-making with oil-pastels along with their relative fluidity, triggering an arousal pattern. Further studies that take the format and presentation of the materials as well as the content of the artwork, into account, are needed.